Taking Stock, December 2017 : An Update on Vietnam’s Recent Economic Developments - World Bank (World Bank, Washington, DC, 2017)
The report examines how Vietnam’s economy has fared in a strengthening global economy in 2017, the drivers of Vietnam’s recent economic performance, growth prospect and the country’s progress in structural reform, among others. It also includes a special section on how to improve efficiency and equity of public spending, as budget deficit is being contained.